Lack of Association Between Partial Y chromosome AZFc-gr/gr Deletions and Male Infertility - Muhsin Jamil Abdulwahid; Mustafa Saber Al-Attar (BioMed Target Journal)
A microdeletion in the azoospermia factor (AZF) region of the human Y chromosome long arm is the second most common genetic factor causing male infertility and spermatogenetic failure. The current study aimed to evaluate the occurrence of AZFc-partial gr/gr deletions in a sample of 260 infertile azoospermia and 40 fertile men as a control group from the Kurdish community using the gel-based PCR technique. To understand whether these deletions were associated with their fertility problems. Two pairs of gr/gr primers (sY1291and sY1191) and a primer of Hetero-chromatin sY160-F were used for screening for gr/gr deletion in a single PCR reaction according to EAA and EMQN protocol. Based on the results of this study, no AZF/c gr/gr deletions were found in either the infertile or fertile participants. Therefore, this finding confirms the concept that these AZFc gr/gr partial deletions are improbable to have an important impact on infertility, and the hereditary risk associated with these partial deletions is much reduced compared to deletions that affect the entire AZFc region.